A Need Analysis Study of Active Reading Book - Hermariyanti Kusumadewi; Eva Nurul Candra (Pusat Penerjemah dan Penyunting Universitas Indraprasta PGRI, 2023)
The purpose of reading skills is not only to look for factors related to reading material i.e. topic and main idea, but also sometimes EFL students must get the latest reading material as the times change in getting those material related with global Sustainable Development Goals (SDGs). Therefore, learning material must be in accordance with the needs of the EFL students, and SDGs represent a broad, integrated to catalyze implementation of sustainable development. The textbook will be analyzed in this research is Reading Comprehension book 2 for 3rd semester written by Parlindungan Pardede published by Unindra. There are many text book evaluation criteria; however, this research will focus in SDGs. The objective of the research is to analysis whether the “Reading Comprehension Skill Book 2 “is considered relevant to the SDGs criteria. In this research, the writer employs a descriptive- quantitative content analysis with qualitative approach. According to analysis, the composition of that textbook shows that this meets the criterion in terms of objectives, that is the objectives laid out in the beginning and proved with the materials that are relevant to, elaborating through standard of curriculum only 32% of the whole materials. Unfortunately, there are many improper materials which are not suitable with KKNI criteria. The explanation among units are not only provided, but also sometimes EFL students must get the latest reading material as the times change in getting those material related with global Sustainable Development Goals (SDGs). Therefore, learning material must be in accordance with the needs of the EFL students, and SDGs represent a broad, integrated to catalyze implementation of sustainable development.